Effect of organic content and cement quantity on the shear behavior of artificially cemented soil. Issue 1 (February 2020) - Hatmoko, J T; Handoko, L
Abstract: Most of the soil in the universe contain organic matter that results on the negative effects on the shear behavior of soil. The objective of this research is to study the effect of organic content and proportion of cement of artificially cemented soil. A compaction and direct shear test without curing period were undertaken on the soil with 6, 11, 16, and 21% organic content. Direct shear test results show that the soil cohesion decrease and internal friction angle slightly increase as increasing of organic content. The direct shear test of artificially cemented soil with 21, 28, 42, and 56 curing time was then performed to investigate the effect of cement quantity on the shear behavior of cemented soil. The cement content was 25, 50, 75, and 100 kg/m 3 . The more cement quantity added to the soil, cohesion and friction angle of artificially cemented soil improves. There is also improvement of the shear stress due to the increase of cement proportion. Similarly, shear strength of stabilized soil improves inherent with curing period due to the short and long-term pozzolanic reactions.